Analisis Keefektifan Sistem Pembayaran Cash on Delivery (COD) di E-Commerce Indonesia - Nia Nia (Jurnal Al-fatih Global Mulia, 2023)
The system of Cash on Delivery (COD) has becoming one of payment method that is favored by Indonesian citizen. The aim of this research is to analyse the effectiveness of COD payment system in Indonesian e-commerce. This research used descriptive qualitative method. The result of this research showed that this system was effective for both seller and buyer, but it was not effective for courier. It was caused the lack of deep information about this system. Thus, it was suggested to  give an extra education such as in TV advertisement.